Craniofacial Surgery Recent Advances, New Perspectives and Applications - Işik Aslan, Belma; Şibar, Serhat (IntechOpen, 2023)
This book provides a comprehensive overview of craniofacial surgery, which is an internationally recognized specialty experiencing tremendous advancements in materials, technology, instrumentation, and treatment methods. This book examines these advancements in detail. Chapters address such topics as regenerative materials in oral surgery, tissue induction in plastic and maxillo-facial surgery, the role of genetics, stem cells, and reconstructive surgery in craniofacial diseases and syndromes, diagnostic and surgical considerations in congenital craniofacial deformities, and assessment of psychological functioning among cleft lip palate patients.